Number of Siblings and Educational Choices of Immigrant Children: Evidence from First- and Second- Generation Immigrants - Dominique Meurs; Patrick Puhani; Friederiki Von Haaren (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
We document the educational integration of immigrant children with a focus on the link between family size and educational decisions and distinguishing particularly between firstand second-generation immigrants and between source country groups. First, for immigrant adolescents, we show family-size adjusted convergence to almost native levels of higher education track attendance from the first to the second generation of immigrants. Second, we find that reduced fertility is associated with higher educational outcomes for immigrant children, possibly through a quantity-quality trade-off. Third, we show that between one third and the complete difference in family-size adjusted educational outcomes between immigrants from different source countries or immigrant generations can be explained by parental background. This latter holds true for various immigrant groups in both France and Germany, two major European economies with distinct immigration histories.
Keywords: J13; J15; J24; 330; migration; integration; quantity-quality trade-off; decomposition